Angular Dependence of the Coercivity in Electrodeposited Co-Pt Nanostructures with a Tube-Wire Morphology - Escrig-Murua, J (Institute of Electrical and Electronics Engineers Inc., 2014)
We have fabricated Co-Pt cylindrical nanostructures comprised of a pair of nanotube and nanowire segments via direct electroplating into anodic alumina (AAO) membranes. The fabrication of such nanostructures is possible due to the penetration of sputtered gold (Au) nanoparticles inside the template, which serve as nucleation spots. The current transient monitored during the deposition process allowed us to distinguish between the nanotube and nanowire formation regime during the electrodeposition. In this paper, we report on the systematic changes in the angular dependence of the coercivity behavior due to the change in the length of the nanowire segment of these nanostructures, while keeping the nanotube segment constant. Considering the range of parameters studied, we found that the tube segment always reverses its magnetization through a vortex domain wall, whereas the nanowire segment reverses its magnetization through a transverse domain wall. Our results are in good agreement with literature. The possibility to alter the magnetization reversal mode in such nanostructures provides an attractive way to control the motion of the magnetic domain walls. © 1965-2012 IEEE.